Conceptual Paper: Factors Affecting the Demand of Smartphone among Young Adult - Chow Mei Min; Chen Ling Hong; Yeow Jian Ai; Wong Pei Wah (International Journal on Social Science, Economics and Art, 2012)
The term ‘Smartphone’ has commonly discussed among young adult especially students from higher learning institutional. Cell phone has becoming a part of their life-tool eventually. Young adult eventually used their phone to communicate with people, alarming themselves from few reminders, direct ways, downloading songs and games, texting messages and more. According to Rice and Katz (2008), the cell phone can be said as a social medium that developing into a multimedia digital platform which has the ability to provides, obtains, and shares personal and social information. However, the market eventually has a higher technology which is called Smartphone. Several industries have hurriedly espoused mobile devices, such as personal digital assistants (PDAs) which have the capabilities of integrating wireless connections and mobile devices that auxiliary pushed the demand effectively in every industry by having a new buzzword, “Smartphone,” illustrates this popular PDA-phone amalgamation with numerous capabilities (Park and Chen, 2007). The factors affecting consumer demand towards Smartphone are complex in nature and usually there is no single factor or simple reason can be determined. Nowadays, consumers tend to shift their preferences from a basic cell phone to a Smartphone. It is obviously the major lead for mobile phone manufacturers to switch the production towards Smartphone due to high demand. The four independent variables under investigation in this study include product features, brand name, price and social influences. The dependent variable is the demand of Smartphone among young adult. Young adults may include fresh graduates with no working experience, industrial trainee from higher learning institutional or students that study in higher learning institutional. In other words, the target respondents are those youngsters whose age falls between 17 to 25. The main objective of this study is to develop a literature review of factors affecting the demand of Smartphone among young adult. This conceptual paper showed a strong relationship between the variables. A pilot test will be carried out to test the reliability of the variables.